2020
DOI: 10.1177/1757913920906845
|View full text |Cite
|
Sign up to set email alerts
|

Using social media for smoking cessation interventions: a systematic review

Abstract: Background: Previous studies have shown that smoking tobacco significantly increases both incidence and mortality rates for many diseases. Social media has become one of the most influential platforms for various smoking cessation interventions. However, results from smoking cessation interventions have differed from study to study. Limited studies have summarised cessation outcomes from social media–based interventions. Therefore, the objective of this review is to explore the effectiveness of using social me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 45 publications
0
23
0
1
Order By: Relevance
“…Social media has become a primary source of news and health information for the majority of adults in the U.S. [14]., with more than 90% of physicians reporting the use of social media for circulating information and education about health [15]. Social media has also been employed in health interventions such as preventing smoking [16] and may be harnessed to improve awareness of foodborne illness [17]. Investigations comparing online news to Twitter about genetically modified (GM) mosquitoes revealed that Twitter discussion was more benefitoriented whilst news media was more balanced [18].…”
Section: Introductionmentioning
confidence: 99%
“…Social media has become a primary source of news and health information for the majority of adults in the U.S. [14]., with more than 90% of physicians reporting the use of social media for circulating information and education about health [15]. Social media has also been employed in health interventions such as preventing smoking [16] and may be harnessed to improve awareness of foodborne illness [17]. Investigations comparing online news to Twitter about genetically modified (GM) mosquitoes revealed that Twitter discussion was more benefitoriented whilst news media was more balanced [18].…”
Section: Introductionmentioning
confidence: 99%
“…Social media (SM) and social networking sites (SNS) are the most popular channel for delivering interventions or knowledge to the targeted groups, as shown in Figure 5 . Although they rely on interactivity, timeliness, and low cost to gain an invaluable advantage in the intervention of smoking cessation ( 88 , 89 , 91 ), blood glucose and pressure control ( 77 , 79 , 85 , 87 ), and HIV antiretroviral treatment adherence ( 76 ), this also inevitably exposes their limitations in terms of both data and the platforms themselves. First, the efficacy and safety of digital interventions are unknown, not only due to the methodological limitations of randomized controlled trials such as small sample size ( 81 ) and absence of critical information ( 77 ), but also due to the nature of SM, that is, uncontrolled sharing of information leading to low data accuracy ( 79 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, proper recommendations from the clinician are necessary and crucial. Second, user engagement and retention are another major concern ( 88 ). The use of social media is entirely voluntary and most of the known data are self-reported by patients, which requires a high degree of self-awareness for people with a chronic disease such as diabetes or hypertension to intervene as designed, making the desired efficacy difficult to achieve.…”
Section: Resultsmentioning
confidence: 99%
“…The techniques most frequently reported for such interventions included the provision of details on how to achieve the modified behavior, social support, self-monitoring of behavior, and information about possible health consequences. Another systematic review focused on interventions to encourage the cessation of smoking found that the interventions making use of social media were as effective as those based on individually designed interactive platforms [ 62 ]. The review of nutritional interventions targeting adolescents and young adults revealed that the majority of interventions that included a social media component achieved positive outcomes [ 63 ].…”
Section: Discussionmentioning
confidence: 99%